Unbuilding - Macaulay, David (Boston : Houghton Mifflin, 1980)
This fictional account of the dismantling and removal of the Empire State Building describes the structure of a skyscraper and explains how such an edifice would be demolished.
Wilson's Children
Wilson's Senior High School
Wilson's Junior High School
Young Adult
Keywords: Empire State Building (New York, N.Y.) -- Juvenile literature; Wrecking -- Juvenile literature; Empire State Building (New York, N.Y.); Wrecking; Skyscrapers; Empire State Building (New York, N.Y.); Skyscrapers